The monastery of Santa Clara de Lima - Alegría La Rosa, Lourdes Milagrito (2019)
The monastery of Santa Clara is one of the largest and most prestigious convents founded in the city of Lima during the 17th century, and which continues active even today. This article describes the social role played by women residing in the capital of the Viceroyalty of Peru; the political and social context in which it was immersed when it was founded is analyzed, as well as the motivations of its founders for the creation of this religious institution. Likewise, it is intended to frame the religious institution within the concepts of cultural heritage and tourism.